Current status and future directions of research on facial attractiveness - Kościński, Krzysztof (Anthropological Review, 2009)
The aim of the present paper was to evaluate the current state of knowledge on the perception of facial attractiveness and to assess the opportunity for research on poorly explored issues regarding facial preferences. A theoretical framework of research problems was proposed, within which the current state of knowledge on each topic was estimated. The analysis proved that a disproportional amount of research concerned several topics, while many other topics were addressed by few studies, the results of which being sometimes contradictory. Next, possible obstacles to more comprehensive research are discussed. This leads to the conclusion that the obstacles do not severely hinder investigations of most poorly studied problems. The results of the author's recent studies on some of these topics are also briefly reported. In spite of thousands of studies conducted, facial attractiveness research may be regarded as rather poorly progressed, although prospects for it are good.